Ergonomics product development of over bed table for bedridden patients. Issue 4 (3rd July 2016) - Lin, Than; Ekanayake, Akhila; Gaweshan, Lewis S.; Hasan, Zareer A.
ABSTRACT: The ergonomic design is very important parameter for many products. When designing a human control product, the ergonomics factors should be satisfied to make a product which will not harm the user. Considering ergonomic factors in the design process are really important. This paper presents a design methodology for developing an ergonomics product. The ultimate goal of this research is to design and to produce a new type of over bed table for bedridden patients. A survey has been conducted and the Quality Function Deployment (QFD) was developed. A virtual ergonomic analysis has been implemented in Jack SIEMEN® using virtual human models and anthropometric data. GRAPHICAL ABSTRACT: